Shielding performance of MnxNi0.8–xZn0.2Fe2O4 (0.1≤x≤0.7) for electromagnetic interference (EMI) in X-band frequency. Issue 7 (1st April 2022) - Srinivas, Ch; Naga Praveen, K.; Ranjith Kumar, E.; Chandrasekhar Rao, T.V.; Prajapat, C.L.; Meena, Sher Singh; Bhatt, Pramod; Arun, B.; James Raju, K.C.; Sastry, D.L.
Abstract: A series of Mn x Ni0.8– x Zn0.2 Fe2 O4 (0.1≤ x ≤0.7) nanoferrites were prepared by sol-gel auto combustion method. The TGA-DSC studies revealed the weight loss up to 700 °C and after no weight loss was found confirming the complete ferrite phase. Therefore, the as-burnt samples subjected to conventional sintering at 900 °C for 2h. The traces of XRD patterns revealed that formation of ferrite phase co-existed with secondary phases. The complex permittivity and permeability of present ferrite systems are found to be dependent of Mn 2+ ion concentration. The real part of dielectric constant ( ε ′ ) for the all compositions are in the range of 5.184–6.951 at 8.2 GHz while it is 5.269–7.663 at 12.4 GHz. The values of ε ′ at 8.2 GHz are slightly lower than the values at 12.4 GHz. The imaginary part of dielectric constant ( ε ″ ) was found to be in the range of 0.046–0.315 for all compositions over the entire range of X-band frequency (8.2–12.4 GHz). Compared to the variation of ε ′, the variation of ε ″ is more disorder. The number of semicircles in Cole-Cole plots is a witness of multiple di-electric relaxations of EM energy dissipation. The real part of magnetic permeability ( μ ′ ) is increasing, while imaginary part of magnetic permeability ( μ ″ ) is decreasing for all compositions as frequency is increasing from 8.2 to 12.4 GHz. Compared to the other ferrite compositions, the ferrite with low content of Mn 2+ i.e. Mn0.1 Ni0.7 Zn0.2 Fe2 O4 ferrite system has higher value of μ ″ and seems to be invariant over the entire X-band frequency range. The total effective shielding ( SE T ) for all compositions is found to be in the range 37–12 dB. The highest values of SE T 37 dB at 8.2 GHz and 28 dB at 12.4 GHz were reported for the ferrite composition Mn0.1 Ni0.7 Zn0.2 Fe2 O4 . The shielding studies revealed that Mn–Ni–Zn ferrite systems are effectively suppressing electromagnetic interference (EMI) in X-band frequency. Comparatively, the ferrite system Mn0.1 Ni0.7 Zn0.2 Fe2 O4 is useful for the fabrication of EMI suppressor.